The Effect of Different Feeding Frequencys and Amount of Feeding on the Growth and Survival of Nilem Larvae (Osteochillus hasselti) - Reinaldi, Markus; Sukendi, Sukendi; Aryani, Netti (Jurnal Akuakultur SEBATIN, 2024)
This research was conducted in Desember – January 2021 at the Laboratory of Fish Hatchery and Breeding, Faculty of Fisheries and Marine Sciences, Universitas Riau. This study aims to determine the effect of feeding and the number of different feeds on the growth and survival of Nilem (Osteochillus hasselti) larvae. The method used was a completely randomized factorial design with 9 treatments and 3 replications. F2P25 (Feed Frequency 2 x daily + Total Feed 25% of body weight), F4P25 (Feed Frequency 4 x daily + Total Feed 25% of body weight), F6P25 (Feed Frequency 6 x daily + Total Feed 25% of body weight), F2P50 (Feed Frequency 2 x daily + Total Feed 50% of body weight), F4P50 (Feed Frequency 4 x daily + Total Feed 50% of body weight), F6P50 (Feed Frequency 6 x daily + Total Feed 50% of body weight), F2P75 (Feed Frequency 2 x daily + Total Feed 75% of body weight), F4P75 (Feed Frequency 4 x daily + Total Feed 75% of body weight), F6P75 (Feed Frequency 6 x daily + Total Feed 75% of body weight ). The results showed that different feeds and feeds had a very significant effect on growth with absolute length (3.14 cm), absolute weight (2.70 g), specific growth rate (14.56), and survival rate (87, 77%).